The Effect of Work Environment on Employee Performance at Golden Tulip Jineng Resort Bali - Sihombing, Irene Hanna H.; Elsavitri, Ni Made Nurdiana (Asian Journal of Management Analytics, 2023)
This study aims to determine the effect of the work environment on employee performance at Golden Tulip Jineng Resort Bali. A good work environment can make a positive contribution to employee performance, while a bad work environment may decrease employee performance. The number of samples in this study was 57, using the saturated sampling method. The data was collected by distributing questionnaires using a 5-point Likert scale to measure 27 statement items. The data analysis techniques used were simple linear regression analysis, t-test, and the coefficient of determination, which were processed with the SPSS version 29 for Windows program. The results of this study indicate that the work environment contributes to employee performance by 76.9%, while the remaining 23.1% is influenced by other variables outside of this study. The companies are expected to pay more attention to the work environment to improve the performance of employees.